From the Cover: l-Carnitine via PPARγ- and Sirt1-Dependent Mechanisms Attenuates Epithelial-Mesenchymal Transition and Renal Fibrosis Caused by Perfluorooctanesulfonate. (30th August 2017) - Chou, Hsiu-Chu; Wen, Li-Li; Chang, Chih-Cheng; Lin, Chien-Yu; Jin, Lu; Juan, Shu-Hui
Abstract: We have previously reported that perfluorooctanesulfonate (PFOS) causes cell apoptosis in renal tubular epithelial cells (RTCs). Here, we extend our findings and provide evidence of epithelial-mesenchymal transition (EMT)-associated renal fibrosis caused by PFOS and the protection by l -carnitine. Our results demonstrate that PFOS increased the expression of EMT and renal injury biomarkers (eg, N-cadherin, vimentin, Snail, Kim1, and Lcn2). In addition, PFOS caused EMT induction through Sirt1-mediated PPARγ deacetylation and inactivation. l -carnitine reversed the EMT induction caused by PFOS and alleviated PFOS-mediated increases in cell migration by reactivating PPARγ through the inhibition of Sirt1 activity. The critical role of Sirt1 in this process was validated by using Sirt1 overexpression, resveratrol (a pharmacologic activator of Sirt1), nicotinamide (a Sirt1 inhibitor) and siSirt1. Nicotinamide and siSirt1, but not Sirt1 overexpression and resveratrol, alleviated PFOS-mediated EMT induction, suggesting that increased Sirt1 activity contributed to the alterations. Furthermore, through PPARγ overexpression and pharmacologic interventions, we validated the crucial role of increased PPARγ deacetylation caused by aberrant increased Sirt1 activity in RTC transformation. Similar to PPARγ overexpression, rosiglitazone (a PPARγ agonist) alleviated the effects of PFOS on the EMT-related features, whereas GW9662 (a PPARγ antagonist) mimicked the effects. The protective effect of l -carnitine was also verified in a mouse model of chronic PFOS exposure, in which decreased EMT biomarker levels and renal fibrosis by l -carnitine were observed in Western blot and histological analyses. Accordingly, l -carnitine alleviated EMT-associated renal fibrosis caused by PFOS through a Sirt1- and PPARγ-dependent mechanism.